PSXV-26 Performance and health responses of feedlot receiving cattle supplemented with pre- and probiotic ingredients. (8th October 2021) - Mackey, Shea; Cooke, Reinaldo F; Colombo, Eduardo; Wiegand, Jacob; Pickett, Autumn; Batista, Luiz Fernando Dias; Alhadas, Herlon; Pacheco, Marcos; Proctor, Jarret; Block, Elliot; Brandão, Alice
Abstract: This experiment compared performance and health responses of feedlot cattle receiving a synbiotic supplement (yeast-derived prebiotic + Bacillus subtilis probiotic), which replaced or were fed in conjunction with feed-grade antimicrobials (monensin and tylosin) during a 56-d receiving period. Angus-influenced steers (n = 192) from 4 different sources were transported for 800 km, and arrived on the experimental feedlot on d 0 when shrunk body weight (BW) was recorded. Steers were ranked by source and shrunk BW, and were allocated to 1 of 24 drylot pens. Pens were assigned to receive a free-choice diet containing: 1) monensin and tylosin (RT; 360 mg/steer daily from Rumensin and 90 mg/steer daily from Tylan; Elanco Animal Health, Greenfield, IN), 2) yeast-derived ingredient and B. subtilis probiotic (CC; 18 g/steer daily of Celmanax and 28 g/steer daily of Certillus; Church and Dwight Co., Inc., Princeton, NJ), or 3) monensin and tylosin combined with yeast-derived and B. subtilis ingredients (RTCC) as in RT and CC. Feed intake was greater (P < 0.01) in CC compared with RT and RTCC cattle (7.34, 6.15, 6.22 kg of dry matter/head daily, respectively; SEM = 0.29). Average daily gain tended (P ≤ 0.10) to be greater in CC compared with RT and RTCC cattle (1.23, 1.16, 1.16 kg/d, respectively; SEM = 0.03). Feed efficiency was less in CC compared with RT and RTCC cattle (0.160, 0.173, 0.171 kg/kg, respectively; SEM = 0.003). Incidence of bovine respiratory disease did not differ (P = 0.37) between treatments (25.9, 20.2, and 15.5% for CC, RT, and RTCC, respectively; SEM = 5.2) during the 56-d receiving period. Collectively, replacing RT with CC improved feed intake and BW gain during a 56-d receiving period, despite reducing feed efficiency. Combining RT and CC ingredients, however, did not yield additional productive and health benefits to receiving cattle.